Wyjść poza reżim imperatywu rozwojowego. Między inspiracjami Rousseau a wpływem myśli Foucaulta na współczesne studia nad dzieciństwem - Dorota Klus-Stańska (Problemy Wczesnej Edukacji)
The text is an attempt at a comparative analysis of the concept by Rousseau in which he proposed moving away from the directive control of the development of the child, with those concepts that can be found in poststructural childhood psychology and pedagogy, whose authors are inspired by the work of Michel Foucault. The author reconstructs the incidents of the child’s crying (Book 2) and child’s agency (Book 3) described in “Emile”, to show that Rousseau’s proposition is, in reality, manipulative and oppressive in relation to the child, being as it is based upon the all-knowing mentor, who carries out his own hidden programme. The poststructural proposition frees childhood from the regime of standardization and normalisation, taking as its starting point a problematisation of so-called, scientific developmental psychology, questioning the very term development and the role of educational institutions. The fundamental difference between the concept of the right of the child to enjoy their life in freedom formulated by Rousseau and poststructuralist concepts, is identified by the author in terms of four areas: certainty “versus” the uncertainty of deciding(differences in status given to the thesis and the project, universalism “versus” localism (differences in scope of agreed upon understandings), binary “versus” diversity (differences in accepted ontological assumptions), instruction “versus” description (differences in moral attitude towards the child).